Cortical circuits for transforming whisker sensation into goal-directed licking. (December 2020) - Esmaeili, Vahid; Tamura, Keita; Foustoukos, Georgios; Oryshchuk, Anastasiia; Crochet, Sylvain; Petersen, Carl CH
Highlights: Primary whisker sensory cortex signals to diverse downstream brain areas. Licking-related motor cortex receives sensory and higher-order motor inputs. Whisker sensory circuits excite licking motor circuits after reward-based learning. Acetylcholine and dopamine reward signals might gate synaptic plasticity. Abstract : Animals can learn to use sensory stimuli to generate motor actions in order to obtain rewards. However, the precise neuronal circuits driving learning and execution of a specific goal-directed sensory-to-motor transformation remain to be elucidated. Here, we review progress in understanding the contribution of cortical neuronal circuits to a task in which head-restrained water-restricted mice learn to lick a reward spout in response to whisker deflection. We first examine 'innate' pathways for whisker sensory processing and licking motor control, and then discuss how these might become linked through reward-based learning, perhaps enabled by cholinergic-gated and dopaminergic-gated plasticity. The aim is to uncover the synaptically connected neuronal pathways that mediate reward-based learning and execution of a well-defined sensory-to-motor transformation.